A Casa das Crianças: Três Modelos de Espaços Escolares Montessori - Mariana Costa Abreu (2021)
School is a coonection place between humans and their surroundings, it is more than a place to teache. It is the shelter that welcomes and promotes both an educational and a growth process. The relation between architecture and pedagogy is understood as a pedagogical instrument and this relation is intensifed by changes in society, which in turn have infuenced the design of the teaching space. From the 19th and 20th century, the introduction of new teaching methods resolted in new way of looking at children and in a growing concern with pedagogy. This happened as a refeccion of introducing new teaching methods. These inovative models block the rigidity of traditional models and nowadays, they're not so recognized. Montessori schools represent this new way of looking at education created by Maria Montessori, where childrens are indepent beings and are the center of the educational process. This pedagogy is known by being complex and designed to detail to satisfy the need of autonomous beings. Just like the space for them. At the same time, the main characteristic of the new education is freedom, that is refected in the architectural space too, with fexible spaces that allow childrens apropriation. Montessori Pedagogy requires a teaching environment that encourages learning, giving the child the independence needed in today's society. So, this master's thesis, Chindren's Space: Tree Models of Montessori Schools, shows how architecture to the Montesssori Method principles, throught various study cases like: Children's House in Viena (1922) by Franz Schuster, a primary Montessori School in Delft (1960/66) by Herman Hertzberguer and the Fuji Kindergarten designed by Tezuka Architects (2007). The study of these and more cases, revealed the Montessori Spaces through themes like:The Schhol and the City, The School distribution, The Montessory Classroom and The Outdoor Space.